Transparent moisture absorption laminate

The transparent hygroscopic laminate with a hydrotalcite-based moisture absorbent and specific binder resins addresses the issues of moisture resistance and transparency in packaging, ensuring effective moisture absorption and content protection.

JP2025007830APending Publication Date: 2025-01-17DAI NIPPON PRINTING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023109481
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Conventional packaging materials for pharmaceuticals and foods lack sufficient moisture resistance, transparency, and stability, leading to issues such as deterioration of contents and safety risks from desiccants, while existing rust-preventing laminates may cause unwanted effects and reduce visibility.

Method used

A transparent hygroscopic laminate comprising a gas barrier layer, a base material layer, and a hygroscopic sealant layer with a hydrotalcite-based moisture absorbent and specific binder resins, ensuring high moisture absorption and transparency without volatile agents.

Benefits of technology

The laminate provides excellent moisture absorption, maintaining transparency and preventing content deterioration, while eliminating safety risks associated with desiccants and volatile agents, and enhancing visibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007830000001_ABST
    Figure 2025007830000001_ABST
Patent Text Reader

Abstract

To provide a transparent moisture absorption laminate which is excellent in production suitability, is excellent in moisture absorption while having a simple layer constitution, is excellent in visibility of a content due to excellent transparency even before and after moisture absorption, shields moisture from outside, absorbs moisture in a packaged content storage part space, and can prevent a content from being degraded by moisture during transportation and storage for a long period of time, and a transparent moisture absorption packaging material and a transparent moisture absorption package which are produced using the transparent moisture absorption laminate.MEANS FOR SOLVING THE PROBLEM: A transparent moisture absorption laminate has at least a gas barrier layer, a base material layer, and a transparent moisture absorption sealant layer containing a moisture absorption layer and a heat seal layer in this order in a laminated manner, wherein the moisture absorption layer contains at least a specific moisture absorption agent and binder resin, and is excellent in high moisture absorption, high whole light transmittance and a low haze.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent moisture-absorbing laminate that is transparent and has moisture-absorbing properties for suppressing moisture absorption of packaged contents, and to a transparent moisture-absorbing packaging material and a transparent moisture-absorbing package made using the transparent moisture-absorbing laminate. The transparent moisture-absorbing laminate of the present invention can be applied to products in various fields that dislike moisture, and can be suitably used, for example, as a packaging material for preventing rust on metal products such as vehicle screws, shafts, and metal plates, and electrical components, and as a packaging material for suppressing deterioration due to moisture in foods, medicines, etc. [Background technology]

[0002] Many conventional packaging materials for medicines and foods that are sensitive to moisture do not have sufficient moisture-proofing, so to compensate for this, aluminum foil pillow bags are used as outer bags and desiccants are also included. However, the moisture-proofing properties are insufficient after the outer bag is opened, and there have been many cases of people accidentally ingesting the desiccant that is included with the product. As a result, packaging bags have been developed for the purpose of transporting or long-term storing medicines and food, and there is a demand for packaging materials that have more stable moisture-proof, waterproof and barrier properties and that have a simple layer structure and can be produced through a manufacturing process with a small number of steps so as to maintain the quality of the medicines and food contents. For example, Patent Documents 1 to 3 propose packaging laminates in which a highly volatile rust inhibitor that volatilizes at room temperature and exerts a rust-preventing effect is contained in a resin for the purpose of preventing rust on metal product contents. However, there are concerns that the rust-preventive agent may have effects other than its rust-preventive effect, such as the need for a sealed exterior and that if the vaporized rust-preventive agent comes into contact with the contents, the contents may deteriorate or functionally be impaired. In addition, the removal of the rust-preventive agent is time-consuming and cumbersome, so that its applications are limited. Therefore, there is a demand for rust-preventive laminates that do not use volatile rust-preventive agents. In order to improve the moisture resistance of a packaging material, Patent Document 4 proposes incorporating a desiccant or a barrier layer into the packaging material. However, the transparency of the packaging material is insufficient, and the visibility for checking the deterioration state of the contents is poor. In addition, it has been proposed in Reference 5 to incorporate a moisture absorbent of approximately 100 nm in size into a packaging material to increase transparency. However, the moisture absorbent causes secondary aggregation, making it difficult to obtain high transparency. In addition, in order to increase transparency, the content of the moisture absorbent must be reduced, making it difficult to obtain sufficient moisture absorption capacity. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-254350 A [Patent Document 2] JP 2007-308726 A [Patent Document 3] JP 2010-052751 A [Patent Document 4] Patent No. 5429948 [Patent Document 5] JP 2021-147086 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention aims to solve the above problems and to provide a transparent moisture-absorbing laminate that has excellent manufacturability, has a simple layer structure while having excellent moisture absorption properties, and has excellent transparency both before and after moisture absorption, thereby providing excellent visibility of the contents, blocks moisture from the outside, absorbs moisture in the packaged contents storage space, and can suppress deterioration of the contents due to moisture during transportation and long-term storage, as well as a transparent moisture-absorbing packaging material and a transparent moisture-absorbing package produced using the transparent moisture-absorbing laminate. [Means for solving the problem]

[0005] As a result of various investigations, the present inventors have found that the above object can be achieved by a transparent moisture-absorbing laminate including at least a moisture-absorbing layer containing a specific moisture absorbent and a specific binder resin. That is, the present invention is characterized in the following points. 1. A transparent moisture-absorbing laminate having at least a gas barrier layer, a base layer, and a transparent moisture-absorbing sealant layer including a moisture-absorbing layer and a heat seal layer, laminated in this order, The moisture absorbing layer contains at least a moisture absorbent and a binder resin, The moisture absorbent is hydrotalcite, The content of hydrotalcite in the moisture absorption layer is 0.5% by mass or more and 70% by mass or less, In moisture absorption treatment at 25℃50% for 11 days, Moisture absorption: 2.8g / m 2 That's all. The total light transmittance before and after the moisture absorption treatment is 60% or more and 99% or less. The haze before and after the moisture absorption treatment is 10% or more and 85% or less. A transparent moisture-absorbing laminate. 2. The gas barrier layer includes an inorganic vapor deposition layer, The inorganic vapor deposition layer contains one or more inorganic compounds consisting of aluminum and / or silicon. 2. The transparent moisture-absorbing laminate according to claim 1. 3. The transparent moisture-absorbing laminate according to item 1 or 2 above, wherein the base layer contains a polyamide resin and / or a polyester resin. 4. The transparent moisture-absorbing laminate according to any one of 1 to 3 above, wherein the binder resin contains a polyolefin resin. 5. The transparent moisture-absorbing laminate according to any one of 1 to 4 above, which contains an antioxidant other than a phenol-based antioxidant. 6. The transparent moisture-absorbing laminate according to any one of 1 to 5 above, further comprising a heat seal layer adjacent to one or both sides of the moisture-absorbing layer. 7. A transparent moisture-absorbing packaging material produced from the transparent moisture-absorbing laminate according to any one of 1 to 6 above. 8. A transparent moisture-absorbing packaging body produced from the transparent moisture-absorbing packaging material according to 7 above. Effect of the Invention

[0006] According to the present invention, it is possible to obtain a transparent moisture-absorbing laminate which has excellent manufacturability, has a simple layer structure, yet has excellent moisture absorption properties, and has excellent transparency both before and after moisture absorption, thereby allowing excellent visibility of the contents, blocks moisture from the outside, absorbs moisture in the packaged contents storage space, and can prevent the contents from deteriorating due to moisture during transportation and long-term storage, as well as a transparent moisture-absorbing packaging material and a transparent moisture-absorbing packaging product made using the transparent moisture-absorbing laminate. By using the transparent moisture-absorbing package of the present invention for packaging medicines, deterioration and discoloration of the medicines can be suppressed. In addition, there is no need to include a moisture-absorbing sachet containing silica gel or the like, and the risk of accidentally ingesting the moisture-absorbing sachet can be avoided. Furthermore, the risk of losing tablets, dropping them, or identifying broken tablets can be reduced. Furthermore, when the contents are metal products such as metal equipment, rusting of the metal products can be prevented, eliminating the need to protect the metal products with oiled paper or the like that has been used conventionally. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view showing an example of the layer structure of a transparent moisture-absorbing laminate and a transparent moisture-absorbing packaging material of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another embodiment of the layer structure of the transparent moisture-absorbing laminate and transparent moisture-absorbing packaging material of the present invention.

[0008] In each drawing, the size and ratio of the components may be changed or exaggerated for ease of understanding. Also, for ease of understanding, parts that are unnecessary for the explanation or repeated reference numerals may be omitted. Although not shown in the drawings, an adhesive layer may be provided between each layer. Furthermore, if necessary, in order to strengthen the adhesive strength (adhesion strength) between each layer, the laminated surfaces of each layer may be previously subjected to a physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or a chemical surface treatment such as oxidation treatment using chemicals. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The transparent moisture-absorbing laminate, the transparent moisture-absorbing packaging material, and the transparent moisture-absorbing packaging body of the present invention will be described in more detail below. Specific examples will be given, but the present invention is not limited thereto. In the present invention, the terms film and sheet are used synonymously, and water absorption or moisture absorption refers to the absorption of gaseous and / or liquid water.

[0010] I. Transparent moisture-absorbing laminate The transparent moisture-absorbing laminate of the present invention is a laminate having at least a gas barrier layer, a substrate layer, and a transparent moisture-absorbing sealant layer including a moisture-absorbing layer and a heat seal layer, in this order. Each layer may be a single layer or a multilayer. The transparent moisture-absorbing sealant layer may be, for example, a moisture-absorbing layer having heat-sealing properties, or may have a layer structure having a heat-sealing layer on one or both sides of the moisture-absorbing layer. The transparent moisture-absorbing laminate of the present invention has a gas barrier layer, which makes it possible to inhibit the passage of water vapor that attempts to pass through, and also has a transparent moisture-absorbing sealant layer, which makes it possible to capture the water vapor that has passed through. The transparent moisture-absorbing laminate of the present invention can exhibit transparency both before absorbing moisture and after absorbing moisture, such as by leaving the laminate stationary for 11 days in an environment at a temperature of 25°C and a humidity of 50% RH, or at a temperature of 40°C and a humidity of 90% RH.

[0011] The moisture absorption amount of the transparent moisture-absorbing laminate of the present invention is, for example, 2.8 g / m when left to stand for 11 days under an environment of 25°C and 50% humidity. 2 If the moisture absorption amount is smaller than the above range, it is likely to be difficult to suppress deterioration of the contents, and it is substantially difficult to obtain a moisture absorption amount larger than the above range.

[0012] The transparent moisture-absorbing laminate of the present invention may further contain an antioxidant other than the phenol-based antioxidant.

[0013] In the transparent moisture absorbing laminate of the present invention, the moisture absorbent is fine and the difference in refractive index between the moisture absorbent and the binder resin is small, so that interfacial reflection and scattering are suppressed and high transparency is obtained.

[0014] The lower limit of the total light transmittance of the transparent moisture-absorbing laminate of the present invention is preferably 60% or more, more preferably 80% or more, both before and after moisture absorption. If the total light transmittance is lower than the above range, the transparency is likely to decrease. The upper limit is most preferably 100%, but substantially, it is preferably 99% or less, and more preferably 95% or less. Here, the total light transmittance refers to the light transmittance measured using a color information measuring device or the like according to the method specified in JIS K7361 (Testing method for optical properties of plastics).

[0015] The haze of the transparent moisture absorbing laminate of the present invention is preferably 85% or less, more preferably 70% or less, and even more preferably 30% or less, both before and after moisture absorption. If the haze is greater than the above range, the transparency is likely to decrease. The lower limit is most preferably 0%, but substantially, it is preferably 10% or more, and more preferably 14% or more.

[0016] If the transparent moisture-absorbing laminate lacks support (rigidity), it may further include a reinforcing layer.

[0017] The thickness of the transparent moisture-absorbing laminate of the present invention is not particularly limited, but is preferably 200 μm or more and 500 μm or less, and more preferably 250 μm or more and 400 μm or less. If it is thinner than the above range, it is difficult to fully exhibit the moisture absorption effect and the moisture absorption effect resulting therefrom, and if it is thicker than the above range, the moisture absorption effect is not improved so much, and the rigidity of the transparent moisture-absorbing laminate becomes too strong, which tends to make it difficult to use as a packaging material and tends to reduce transparency. The layers constituting the transparent moisture-absorbing laminate may be laminated via an adhesive layer or an anchor coat layer.

[0018] <Method of manufacturing transparent moisture-absorbing laminate> A method for producing the transparent moisture-absorbing laminate of the present invention will be described below. The method for producing the transparent moisture-absorbing laminate shown below is one example and is not intended to limit the present invention. The formation and lamination of each layer constituting the transparent moisture-absorbing laminate can be carried out by any method, such as wet lamination, dry lamination, solventless dry lamination, extrusion lamination, T-die coextrusion molding, coextrusion lamination, inflation molding, and the like. When the above lamination is performed, if necessary, the surface of each layer may be subjected to a pretreatment such as corona treatment, ozone treatment, etc. Also, anchor coating agents such as isocyanate (urethane), polyethyleneimine, polybutadiene, and organic titanium, or anchor coating agents such as polyurethane, polyacrylic, polyester, epoxy, polyvinyl acetate, cellulose, and other lamination adhesives may be used as desired.

[0019] For example, when preparing a transparent moisture-absorbing laminate having a layer structure of gas barrier layer / adhesive layer / substrate layer / adhesive layer / transparent moisture-absorbing sealant layer [heat seal layer 1 / moisture-absorbing layer / heat seal layer 2], it can be prepared as follows. First, a resin composition for the heat seal layer 1, a resin composition for the moisture absorbing layer, and a resin composition for the heat seal layer 2 are formed into films and laminated by a co-extrusion lamination method to produce a transparent moisture absorbing film for the transparent moisture absorbing sealant layer. Then, the resin film for the gas barrier layer, the resin film for the base layer, and the transparent moisture-absorbing film for the transparent moisture-absorbing sealant layer obtained above are bonded together via a resin composition for the adhesive layer to produce a transparent moisture-absorbing laminate. The obtained transparent moisture-absorbing laminate can also be subjected to secondary processing for the purpose of imparting surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, and biocompatibility, within the scope that maintains transparency and moisture absorption properties.

[0020] Examples of secondary processing include embossing, painting, adhesives, printing, metallizing (plating, etc.), machining, surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromic treatment, physical vapor deposition, chemical vapor deposition, coating, etc.) Transparent moisture absorbing sealant films can also be subjected to lamination (dry lamination and extrusion lamination), bag making, and other post-processing processes.

[0021] <About each layer of the transparent moisture-absorbing laminate>

[0022] I-1. Gas barrier layer The gas barrier layer is a layer that suppresses the permeation of gas. The gas barrier layer preferably includes a transparent inorganic vapor deposition layer. The gas barrier layer may also be a layer made of a resin film with a transparent inorganic vapor deposition layer, which has a transparent inorganic vapor deposition layer on a supporting resin film.

[0023] (Inorganic vapor deposited layer) Examples of inorganic compounds that form a transparent inorganic vapor deposition layer include inorganic oxides, inorganic nitrides, inorganic carbides, etc. Among these, metal oxides are particularly preferably used. As the inorganic element, a metal element or phosphorus (P) element is preferable. Specific examples of metal elements include aluminum (Al), silicon (Si), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), yttrium (Y), zinc (Zn), vanadium (V), barium (Ba), and chromium (Cr). The above inorganic elements can be used alone or in combination of two or more.

[0024] The average composition of metal oxides is expressed as, for example, SiO X , AlO X MO X (wherein, M represents a metal element, and the value of X varies depending on the metal element.) In the above, when X=0, it is a metal, and the upper limit of the range of X is the value when it is completely oxidized. That is, the range of the value of X is greater than 0, with upper limits, for example, 2 for silicon, 1.5 for aluminum, 1 for magnesium, 1 for calcium, 0.5 for potassium, 2 for tin, 0.5 for sodium, 1.5 for boron, 2 for titanium, 1 for lead, 2 for zirconium, and 1.5 for yttrium.

[0025] In the present invention, the inorganic vapor deposition layer preferably contains one or more inorganic compounds comprising elemental aluminum and / or elemental silicon among the above. A specific example of an inorganic compound containing aluminum element is preferably aluminum oxide in which x is in the range of 1.0 to 2.0, and a specific example of an inorganic compound containing silicon element is preferably silicon oxide in which x is in the range of 0.5 to 1.5. The inorganic vapor deposition layer may contain one or a combination of two or more of these inorganic compounds. The inorganic vapor deposition layer may be one layer or two or more layers. In the case of one layer, it may be formed of one type of inorganic compound or a mixture of two or more types of inorganic compounds. In the case of two layers, layers of the same or different compositions may be laminated, and each layer may be formed of one or more types of inorganic compounds.

[0026] (Resin film supporting inorganic vapor deposition layer) For the supporting resin film of the inorganic vapor deposition layer, it is preferable to use a resin film made of a resin that has excellent mechanical, physical, chemical and other properties, and is particularly strong and tough, and has heat resistance, so that it can withstand the process of forming the metal oxide vapor deposition layer. Suitable resins contained in the support resin film include, for example, polyester resins, polyether resins, polyamide resins, polyimide resins, polyamideimide resins, polyamide-based resins, and polyamide-based resins. Examples of the resin include polyolefin resins, polyvinyl chloride resins, (meth)acrylic resins, polycarbonate resins, polyaryl resins, polyurethane resins, polyacetal resins, cellulose resins, polysulfone resins, silicone resins, fluorine resins, and the like. Specific examples of polyester resins include polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). Specific examples of the polyether resin include polyethersulfone resin and polyphenylene sulfide resin. Specific examples of polyolefin resins include polyethylene resins, polypropylene resins, cyclic polyolefin resins, polybutene resins, polystyrene resins, acrylonitrile-styrene copolymers (AS resins), and acrylonitrile-butadiene-styrene copolymers (ABS resins). Specific examples of polyvinyl chloride resins include polyvinyl chloride and polyvinylidene chloride. Specific examples of the (meth)acrylic resin include poly(meth)acrylic acid resins and poly(meth)acrylic acid ester resins. A specific example of the polyaryl resin is a polyaryl phthalate resin. These resins may be used alone or in combination of two or more, or may be used in multiple layers containing different types of resins. In the present invention, among these, it is particularly preferable to contain a polyester-based resin and / or a polyamide-based resin.

[0027] (Method of forming inorganic vapor deposition layer) As a method for forming an inorganic vapor deposition layer on a support resin film, the inorganic vapor deposition layer can be formed on the inorganic vapor deposition layer support film using, for example, a physical vapor deposition method (Physical Vapor Deposition method, PVD method) such as a vacuum deposition method, a sputtering method, an ion plating method, a cluster ion beam method, or a chemical vapor deposition method (Chemical Vapor Deposition method, CVD method) such as a plasma chemical vapor deposition method, a thermal chemical vapor deposition method, a photochemical vapor deposition method, or the like, using the above-mentioned metals or metal oxides as raw materials. More specifically, in the above-mentioned PVD method, for example, a take-up type deposition machine is used, and the inorganic deposition layer support film coming out from a winding roll in a vacuum chamber is placed in a deposition chamber, where the deposition source heated in a crucible is evaporated, and further, if necessary, an inorganic deposition layer is formed through a mask on the resin film on a cooled coating drum while oxygen or the like is sprayed from an oxygen outlet, and then the gas barrier film with the inorganic deposition layer formed thereon is wound up on a take-up roll, thereby producing a resin film having an inorganic deposition layer according to the present invention.

[0028] Meanwhile, in the above-mentioned CVD method, a gas barrier film can be produced in which a mixed gas of, for example, an organosilicon compound as a monomer gas, oxygen gas, and an inert gas, supplied from a vapor deposition raw material volatilization and supply device, is introduced onto the surface of a resin film unwound from a winding roll arranged in a vapor deposition chamber, on the peripheral surface of a cooling electrode drum in the vapor deposition chamber, and an inorganic vapor deposition layer made of silicon oxide is formed by plasma.

[0029] In order to obtain sufficient gas barrier properties, the thickness of the inorganic vapor deposition layer is preferably 50 Å to 3000 Å, more preferably 100 Å to 2000 Å, and even more preferably 100 Å to 1000 Å. More specifically, in the above PVD method, the thickness of the inorganic vapor deposition layer made of aluminum oxide is preferably 200 Å to 1000 Å, and more preferably about 300 Å to 500 Å. In the above CVD method, the thickness of the inorganic deposition layer made of silicon oxide is 50 Å to 5 00 Å is preferable, and 100 Å to 300 Å is more preferable. If the thickness is greater than the above range, cracks or the like are likely to occur in the inorganic vapor deposition layer, which may result in a decrease in gas barrier properties, and the process time is lengthened, which is undesirable since the productivity decreases. Also, if the thickness is smaller than the above range, it is likely to be difficult to achieve sufficient gas barrier properties.

[0030] I-2. Base material layer The substrate layer preferably contains a polyamide-based resin and / or a polyester-based resin. Furthermore, the substrate layer is preferably made of a resin film containing the above-mentioned resin.

[0031] The substrate layer may be configured with multiple layers having the same or different compositions, and layers within the substrate layer may be laminated via an adhesive layer. In addition, the base layer may be laminated directly to other layers such as a gas barrier layer, a transparent moisture-absorbing sealant layer (moisture-absorbing layer, heat seal layer), and a reinforcing layer, or may be laminated via an adhesive layer, an anchor coat layer, or the like.

[0032] The total light transmittance of the base layer is preferably 60% or more and 99% or less, more preferably 65% ​​or more and 95% or less. If it is lower than the above range, the transparency of the transparent moisture-absorbing laminate as a whole tends to be poor, and it is easy to make it difficult to visually confirm the contents. It is difficult to increase it above the above range, and the production process and quality control become complicated, which tends to reduce productivity.

[0033] The haze of the base layer is preferably 0% or more and 70% or less, more preferably 0% or more and 30% or less, before and after moisture absorption. If it is higher than the above range, the transparency of the entire transparent moisture-absorbing laminate tends to be poor, and it is easy to make it difficult to visually confirm the contents.

[0034] (Polyamide resin) Specific examples of the polyamide resin for the base layer include nylon 6, nylon 66, nylon 610, etc., and these polyamide resins may be used alone or in combination of two or more.

[0035] (Polyester resin) Specific examples of polyester-based resins for the base layer include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polyethylene terephthalate-isophthalate copolymer, terephthalic acid-cyclohexanedimethanol-ethylene glycol copolymer, and co-extrusion films of polyethylene terephthalate / polyethylene naphthalate. These polyester-based resins may be used alone or in combination of two or more.

[0036] I-3. Transparent moisture-absorbing sealant layer The transparent moisture-absorbing sealant layer is a layer laminated on at least one surface of the transparent moisture-absorbing laminate, and has moisture-absorbing properties and heat-sealing properties. The transparent moisture-absorbing sealant layer may be a single layer consisting of only a moisture-absorbing layer having heat-sealing properties, or may have a heat-sealing layer on one or both sides of the moisture-absorbing layer. The transparent moisture-absorbing sealant layer is preferably formed from a transparent moisture-absorbing sealant film having the layer structure described above, and may further include other layers.

[0037] The thickness of the transparent moisture-absorbing sealant layer is preferably 50 μm or more and 200 μm or less, more preferably 80 μm or more and 150 μm or less, so that the transparent moisture-absorbing laminate exhibits good heat-sealing properties, appropriate rigidity, and moisture absorption properties as required. If the thickness is thinner than the above range, the heat-sealing properties and moisture absorption properties may be insufficient, and if the thickness is thicker than the above range, the heat-sealing properties and moisture absorption properties may not be significantly improved, and the rigidity may become too strong, resulting in a decrease in workability.

[0038] The transparent moisture absorbing sealant layer may contain any additives within the range that does not significantly impair the effects of the present invention. Examples of the additives include various resin additives that are generally used to adjust the moldability, productivity, and various physical properties of the resin film, such as antiblocking agents, slip agents, pigments, flow control agents, flame retardants, fillers, ultraviolet absorbers, and surfactants.

[0039] Furthermore, the transparent moisture absorbing sealant layer can be subjected to secondary processing for the purpose of imparting surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, and biocompatibility. Examples of secondary processing include embossing, painting, adhesives, printing, metallizing (plating, etc.), machining, surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromic treatment, physical vapor deposition, chemical vapor deposition, coating, etc.), and the like.

[0040] The moisture absorption amount of the transparent moisture absorbing sealant layer is, for example, 2.8 g / m2 under an environment of 25°C and 50% humidity for 11 days. 2 If the moisture absorption amount is smaller than the above range, it tends to be difficult for the transparent moisture-absorbing laminate to suppress deterioration of the contents, and it is substantially difficult to obtain a moisture absorption amount larger than the above range.

[0041] The lower limit of the total light transmittance of the transparent moisture-absorbing sealant layer before and after moisture absorption is preferably 60% or more, more preferably 75% or more. If the total light transmittance is lower than the above range, the transparency of the transparent moisture-absorbing laminate is likely to decrease. The upper limit is most preferably 100%, but substantially, it is preferably 99% or less, and more preferably 95% or less. Here, the total light transmittance refers to the light transmittance measured using a color information measuring device or the like according to the method specified in JIS K7361 (Testing method for optical properties of plastics).

[0042] The haze of the transparent moisture absorbing sealant layer is preferably 90% or less, more preferably 85% or less, both before and after moisture absorption. If the haze is greater than the above range, the transparency of the transparent moisture absorbing laminate is likely to decrease. The lower limit is most preferably 0%, but substantially, it is preferably 10% or more, and more preferably 14% or more.

[0043] [Moisture absorption layer] The moisture absorbing layer is a layer containing a moisture absorbing agent and a binder resin, and the moisture absorbing agent is dispersed in the binder resin. The moisture absorbing layer may contain a thermoplastic resin other than the binder resin to the extent that the transparency, moisture absorption property, dispersibility, and the like are not impaired. The content of the moisture absorbent in the moisture absorbing layer is preferably 0.5% by mass or more and 70% by mass or less, more preferably 0.5% by mass or more and 70% by mass or less of hydrotalcite as the moisture absorbent, even more preferably 20% by mass or more and 60% by mass or less, and particularly preferably 35% by mass or more and 50% by mass or less. If the content is less than the above range, the moisture absorbing effect is likely to be insufficient, and if the content is more than the above range, the film formability is likely to be poor.

[0044] The thickness of the moisture-absorbing layer is not particularly limited, but is preferably 30 μm or more and 150 μm or less, and more preferably 50 μm or more and 100 μm or less. If it is thinner than the above range, it is difficult to fully exert the moisture-absorbing effect, and if it is thicker than the above range, the moisture-absorbing effect is not improved so much, and the rigidity of the transparent moisture-absorbing laminate becomes too strong, which tends to make it difficult to use as a packaging material.

[0045] The moisture absorbent is preferably incorporated into the moisture absorbing layer via a master batch in which the moisture absorbent is melt-blended with a thermoplastic resin. Specifically, it is preferable to prepare a master batch by melt blending the moisture absorbent with a thermoplastic resin at a relatively high concentration, and then dry blending the master batch with a binder resin to obtain a desired concentration in the moisture absorbing layer. The thermoplastic resin to be melt-blended may be one type or two or more types, and may be the same as the binder resin.

[0046] The content of the moisture absorbent in the master batch is preferably 20% by mass or more and 90% by mass or less, and more preferably 30% by mass or more and 70% by mass or less. Within the above range, it is easy to include a necessary and sufficient amount of the moisture absorbent in the moisture absorbing layer in a dispersed state.

[0047] (Moisture absorbent) There is no particular limitation on the number average particle size of the moisture absorbent. However, in order to obtain stable film-forming properties, the number average particle size of the moisture absorbent is preferably 10 μm or less, more preferably 7 μm or less, and even more preferably 1 μm or less. If it is larger than the above range, the film-forming properties tend to decrease, and the transparency of the transparent moisture-absorbing laminate also tends to decrease. The number average particle size of the moisture absorbent is preferably 0.1 μm or more, as it is difficult to stably obtain a moisture absorbent smaller than the above range. There is no particular restriction on the refractive index of the moisture absorbent, but the smaller the difference in refractive index between the moisture absorbent and the binder resin, the greater the transparency of the moisture absorbing layer or transparent moisture absorbing laminate. The difference in refractive index between the moisture absorbent and the binder resin is preferably 0.07 or less. In the present invention, the moisture absorbent preferably contains hydrotalcite.

[0048] (Hydrotalcite) The hydrotalcite used as the moisture absorbent in the present invention includes calcined hydrotalcite and a magnesium oxide-aluminum oxide solid solution obtained by further decomposing the calcined hydrotalcite by heating. Calcined type hydrotalcite is a compound represented by the following formula, which may further contain bound water. Mg 1-x Al x (OH)2(CO3) x / 2 In the above formula, x is a number from 0.1 to 0.4. Magnesium oxide-aluminum oxide solid solution is a compound represented by the following formula, and has a higher hygroscopicity than calcined hydrotalcite. Mg 0.7 Al0.3 O 1.15

[0049] (binder resin) The binder resin is required to be a resin capable of dispersing the moisture absorbent, and may have heat sealability. The binder resin preferably contains a polyolefin-based resin, and among polyolefin-based resins, it is more preferable that it contains a polyethylene-based resin, and among polyethylene-based resins, it is even more preferable that it contains linear low-density polyethylene (LLDPE). The refractive index of polyolefin resin is about 1.49 to 1.54. By including these resins in the binder resin, the moisture absorbent can be dispersed, and stable moisture absorption and transparency can be exhibited.

[0050] (Polyolefin resin) Specific examples of polyolefin resins used as binder resins include polyethylene Examples of suitable resins include ethylene (PE)-based resins, polypropylene (PP)-based resins, polymethylpentene, ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-propylene copolymers, and mixtures of these resins.

[0051] Specific examples of polyethylene resins include low-density polyethylene (LDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), general-purpose polyethylene (general-purpose PE), and polyethylene (PE) copolymers. Among the polyethylene resins, LDPE, LLDPE, general-purpose PE, PE copolymers, etc. are more preferable, and LLDPE is even more preferable.

[0052] (thermoplastic resin) There are no particular restrictions on the thermoplastic resin other than the binder resin contained in the moisture-absorbing layer, so long as it does not significantly reduce the moisture-absorbent dispersibility of the binder resin or the moisture absorption and transparency of the transparent moisture-absorbing laminate and can withstand use as a packaging material, but it is preferable that the thermoplastic resin has excellent heat sealability.

[0053] For example, the thermoplastic resin may be a polyolefin-based resin. Among the polyolefin resins, polyethylene resins and polymethylpentene are more preferable. Specific examples of polyethylene resins include LDPE, MDPE, HDPE, LLDPE, general-purpose PE, and PE copolymers. Among the polyethylene resins, LDPE, LLDPE, general-purpose PE, PE copolymers, etc. are more preferable, and LLDPE is even more preferable.

[0054] (Antioxidants) The transparent moisture-absorbing laminate of the present invention may contain an antioxidant. However, since phenol-based antioxidants tend to cause yellowing of the transparent moisture-absorbing laminate, it is preferable to contain an antioxidant other than a phenol-based antioxidant. Preferred antioxidants include phosphorus-based antioxidants and / or thioether-based antioxidants.

[0055] Specific examples of phosphorus-based antioxidants include ADK STAB PEP-8 (ADEKA), ADK STAB PEP-36 (ADEKA), ADK STAB HP-10 (ADEKA), ADK STAB 2112 (ADEKA), ADK STAB 1178 (ADEKA), ADK STAB 1500 (ADEKA), Irgafos 168 (BASF), and the like.

[0056] Specific examples of thioether-based antioxidants include ADK STAB AO-412S (ADEKA), ADK STAB AO-26 (ADEKA), KEMINOX PLS (Chemipro Chemicals), and RIANOX (Rianlin).

[0057] [Heat seal layer], The heat seal layer contains a heat sealable resin and is a layer having excellent heat sealability. The heat seal layer may contain a moisture absorbent to the extent that the heat sealability is not deteriorated, but the heat sealability is highest when no moisture absorbent is contained, which is preferred. The heat seal layer is preferably laminated adjacent to one or both sides of the moisture absorbing layer.

[0058] (Heat sealable resin) The heat-sealable resin is a resin that has excellent heat-sealing properties. The MFR of the heat-sealable resin contained in the heat-sealable layer is preferably 0.2 g / 10 min or more and 10.0 g / 10 min or less, more preferably 0.5 g / 10 min or more and 7 g / 10 min or less. If it is lower than the above range, the film-forming property and heat-sealing property are likely to be inferior, and if it is higher than the above range, the amount of odorous substances generated due to decomposition of the heat-sealable resin is likely to be high, and yellowing resistance is likely to be inferior.

[0059] Preferred heat-sealable resins include LDPE, MDPE, HDPE, LLDPE, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, ethylene-propylene copolymer, etc., and LLDPE is more preferred. Among the LLDPEs, a single-stage polymerization gas phase metallocene LLDPE is more preferred because of its excellent yellowing resistance. Even though it is the same metallocene-based LLDPE, multi-stage polymerization gas phase LLDPE has a wide molecular weight distribution and contains a lot of low molecular weight components with a polystyrene-equivalent weight average molecular weight of 70,000 or less, so it does not have excellent yellowing resistance. The single-stage polymerization gas phase metallocene-based LLDPE is particularly preferably C6-LLDPE.

[0060] (Single-stage polymerization gas phase metallocene LLDPE) Single-stage polymerization gas-phase metallocene-based LLDPE is LLDPE synthesized by single-stage polymerization in the gas phase using a metallocene catalyst, and has less low molecular weight components than LLDPE synthesized by multi-stage polymerization using conventional Ziegler-Natta catalysts.

[0061] LLDPE is classified into types such as C4-LLDPE, C6-LLDPE, and C8-LLDPE, depending on the type of monomer copolymerized with ethylene. C4-LLDPE is a linear low-density polyethylene consisting of a copolymer of ethylene and 1-butene, C6-LLDPE is a linear low-density polyethylene consisting of a copolymer of ethylene and 1-hexene and / or 4-methyl-1-pentene, and C8-LLDPE is a linear low-density polyethylene consisting of a copolymer of ethylene and 1-octene. C4-LLDPE, C6-LLDPE, and C8-LLDPE have molecular structures in which the ethylene-derived polyethylene main chain has side chains with 4, 6, and 8 carbon atoms derived from 1-butene, 1-hexene and / or 4-methyl-1-pentene, and 1-octene, respectively.

[0062] I-4.Adhesive layer The adhesive used in the adhesive layer in the transparent moisture absorbing laminate may be, for example, an adhesive for DL ​​(dry lamination), an adhesive for EC (extrusion coating), an adhesive for non-solvent lamination, or the like. The adhesive may be of any of the following types: heat-curable, ultraviolet-curable, and electron-beam-curable types; and may be in any form, such as aqueous, solution, emulsion, and dispersion types. The adhesive may be in any form, such as film / sheet, powder, and solid. The adhesive mechanism may be any of the following types: chemical reaction, solvent volatilization, thermal melting, and thermal pressure.

[0063] Examples of components that form such an adhesive layer include polyvinyl acetate resins such as polyvinyl acetate and vinyl acetate-ethylene copolymers, polyacrylic acid resins consisting of copolymers of polyacrylic acid and polystyrene, polyester, polyvinyl acetate, etc., cyanoacrylate resins, ethylene copolymer resins consisting of copolymers of ethylene and monomers such as vinyl acetate, ethyl acrylate, acrylic acid, methacrylic acid, etc., cellulose resins, polyurethane resins, polyester resins, aliphatic polyester polyurethane resins, polyamide resins, and poly Examples of the resin include imide-based resins, polyolefin-based resins such as LDPE, amino resin-based resins such as urea resins or melamine resins, phenolic resin-based resins, epoxy resins, reactive (meth)acrylic resins, elastomer-based resins such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber, silicone resins, and inorganic resins such as alkali metal silicates and low-melting glass.

[0064] II.Transparent moisture-absorbing packaging material The transparent moisture-absorbing packaging material of the present invention is a packaging material made from the transparent moisture-absorbing laminate of the present invention.

[0065] III.Transparent moisture-absorbing packaging The transparent moisture-absorbing package of the present invention is a package produced from the transparent moisture-absorbing laminate or transparent moisture-absorbing packaging material of the present invention. EXAMPLES

[0066] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to these examples.

[0067] <Ingredients> Details of the raw materials used in the examples are as follows. [Moisture absorbent] Moisture absorbent 1: Metal oxide-based moisture absorbent, DHT-4C, manufactured by Kyowa Chemical Industry Co., Ltd. Calcined hydrotalcite (magnesium and aluminum), number average particle size 380 nm, refractive index 1.51. · Moisture absorbent 2: Metal oxide-based moisture absorbent, LT015B, manufactured by Toda Kogyo Co., Ltd. Calcined hydrotalcite (magnesium and aluminum), number average particle size 200 nm, refractive index 1.51. · Moisture absorbent 3: Metal oxide-based moisture absorbent, KW2000, manufactured by Kyowa Chemical Industry Co., Ltd. Hydrotalcite (magnesium and aluminum) solid solution, number average particle size 7 μm, refractive index 1.57. · Moisture absorbent 4: Metal oxide-based moisture absorbent, S-KID ZK50PP, manufactured by Sasaki Chemical Co., Ltd. Calcium oxide. Number average particle size 10 μm, refractive index 1.84.

[0068] [Resin film for gas barrier layer and base layer] · Transparent vapor-deposited PET film 1: PET film with transparent vapor-deposited layer manufactured by Dai Nippon Printing Co., Ltd., IB-PET PXB2. Layer structure: aluminum oxide vapor-deposited layer / PET. 12μm thick. Polyamide film 1: Kohjin Film & Chemicals Co., Ltd., uniaxially oriented polyamide film, Bonyl-W. 15 μm thick.

[0069] [Binder resin] LLDPE1: Prime Polymer LLDPE, SP2020. Density 0.916g / cm 3 , MFR 2.3g / 10min, refractive index 1.50. [glue] Adhesive 1: Polyester / polyol adhesive manufactured by Rock Paint Co., Ltd. Mass ratio: Rockbond J RU77T / Adlock H-7 = 10 / 1.

[0070] <Preparation of Masterbatch> [Preparation of Masterbatches 1 to 4] According to the formulation in Table 1, the moisture absorbent and the binder resin were melt-blended to obtain masterbatches 1 to 4 (MB1 to 4).

[0071] [Table 1]

[0072] <Preparation of Resin Composition for Moisture Absorption Layer>

[0073] [Preparation of Resin Compositions 1 to 4 for Moisture Absorption Layer] According to the description in Table 2, the master batch and the binder resin were dry-blended to obtain resin compositions 1 to 4 for moisture absorbing layer.

[0074] [Table 2]

[0075] <Preparation of film for sealant layer>

[0076] [Preparation of transparent moisture-absorbing film A] Using LLDPE 1 for the heat seal layer 1, resin composition for moisture absorbing layer 1 for the moisture absorbing layer, and LLDPE 1 for the heat seal layer 2, lamination was performed by inflation film formation at 180°C. Next, one surface of the heat seal layer was subjected to a corona treatment to obtain a transparent moisture absorbing film A having the following layer structure. Layer structure: Heat seal layer 1 (15 μm thick, surface corona treatment) / moisture absorption layer (90 μm thick) / heat seal layer 2 (15 μm thick)

[0077] [Preparation of transparent moisture-absorbing films B to C and moisture-absorbing film D] Transparent moisture-absorbing films B to C and moisture-absorbing film D were produced in the same manner as transparent moisture-absorbing film A, except that the type of resin composition for the moisture-absorbing layer and the thickness of each layer were changed as shown in Table 3.

[0078] [Preparation of non-moisture absorbing film E] Using LLDPE1, a film was formed by inflation at 180°C, and one side was subjected to a corona treatment to obtain a non-moisture absorbing film E having a thickness of 60 µm.

[0079] [Table 3]

[0080] (Preparation and evaluation of transparent moisture-absorbing laminate) [Example 1]

[0081] Adhesive 1 was applied to a thickness of 3 μm on the aluminum-deposited layer surface of transparent vapor-deposited PET film 1, and dried. Nylon film 1 was then attached to the adhesive 1-coated surface. Next, adhesive 1 was applied to a thickness of 3 μm on one side of the nylon film, and the corona-treated surface of transparent moisture-absorbing film A was attached to the adhesive 1-coated surface to obtain a transparent moisture-absorbing laminate having the following layer structure. Then, various evaluations were carried out. Layer structure: transparent vapor-deposited PET film 1 [PET layer (12 μm thick) / aluminum vapor-deposited layer] / adhesive 1 (3 μm thick) / nylon film 1 (15 μm thick) / adhesive 1 (3 μm thick) / transparent moisture-absorbing sealant layer [heat seal layer 1 (15 μm thick) / moisture-absorbing layer (90 μm thick) / heat seal layer 2 (15 μm thick)]

[0082] [Examples 2 to 9, Comparative Examples 1 to 6] A transparent moisture-absorbing laminate was produced in the same manner as in Example 1, except that the film for the transparent moisture-absorbing sealant layer was changed according to the description in Tables 4 and 5, and was evaluated in the same manner.

[0083] <Evaluation method>

[0084] [Film forming property] The appearance of the film for the transparent moisture absorbing sealant layer was observed with the naked eye, and the presence or absence of defects was evaluated according to the following evaluation criteria. ◯: No wrinkles, bumps, or peeling. Passed. △: There were some wrinkles, bumps, and peeling. Passed. ×: Many wrinkles, bumps, and peeling were observed. Failed.

[0085] [Moisture absorption amount] The film for the transparent moisture-absorbing sealant layer or the transparent moisture-absorbing laminate was cut to a size of 100 mm length×100 mm width to prepare a test piece. The obtained test piece was left to stand for 11 days in an environment of 25°C temperature and 50% RH humidity, and the weight change of the test piece was calculated as 1 m 2 The amount of moisture absorbed per unit was determined.

[0086] [Total light transmittance and haze] The film for the transparent moisture-absorbing sealant layer or the transparent moisture-absorbing laminate was cut to a size of 50 mm length×50 mm width to prepare a test piece. The total light transmittance and haze of the test pieces before and after moisture absorption (left to stand for 11 days in an environment of 25°C temperature and 50% RH) were measured using a color information measuring device, a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.), in accordance with JIS K7361 (Testing method for optical properties of plastics).

[0087] [Water vapor permeability] Using a Hitachi High-Tech Mocon oxygen permeability measuring device, the water vapor permeability of the film for a transparent moisture-absorbing sealant layer or the transparent moisture-absorbing laminate was measured at 40°C and 90% humidity before and after moisture absorption (left to stand for 11 days in an environment of 25°C and 50% RH).

[0088] [Table 4]

[0089] [Table 5]

[0090] <Summary of Results> All examples showed a good balance of high moisture absorption, high transparency (high total light transmittance and low haze) before and after moisture absorption, and low water vapor permeability. On the other hand, Comparative Example 1, in which a moisture absorbent not containing hydrotalcite was used, exhibited poor transparency, and Comparative Example 2, in which no moisture absorbent was used, exhibited poor moisture absorption. [Explanation of symbols]

[0091] 1. Transparent moisture-absorbing laminate, transparent moisture-absorbing packaging material 2 Base material layer 3 Gas barrier layer 4 Adhesive layer 5 Transparent moisture absorbing sealant layer 6 Moisture absorption layer 7 Heat seal layer

Claims

1. A transparent moisture-absorbing laminate having at least a gas barrier layer, a base layer, and a transparent moisture-absorbing sealant layer including a moisture-absorbing layer and a heat seal layer, laminated in this order, The moisture absorbing layer contains at least a moisture absorbent and a binder resin, The moisture absorbent is hydrotalcite, The content of hydrotalcite in the moisture absorption layer is 0.5% by mass or more and 70% by mass or less, In a moisture absorption treatment at 25°C and 50% humidity for 11 days, Moisture absorption is 2.8 g / m 2 That's all. The total light transmittance before and after the moisture absorption treatment is 60% or more and 99% or less, The haze before and after the moisture absorption treatment is 10% or more and 85% or less. A transparent moisture-absorbing laminate.

2. The gas barrier layer includes an inorganic vapor deposition layer, The inorganic vapor deposition layer contains one or more inorganic compounds consisting of aluminum and / or silicon.

2. The transparent moisture-absorbing laminate according to claim 1 .

3. 2. The transparent moisture-absorbing laminate according to claim 1, wherein the substrate layer contains a polyamide resin and / or a polyester resin.

4. The transparent moisture-absorbing laminate according to claim 1 , wherein the binder resin contains a polyolefin resin.

5. 2. The transparent moisture-absorbing laminate according to claim 1, further comprising an antioxidant other than a phenol-based antioxidant.

6. 2. The transparent moisture-absorbing laminate according to claim 1, further comprising a heat seal layer adjacent to one or both sides of said moisture-absorbing layer.

7. A transparent moisture-absorbing packaging material produced from the transparent moisture-absorbing laminate according to any one of claims 1 to 6.

8. A transparent moisture-absorbing package made from the transparent moisture-absorbing packaging material according to claim 7.

Citation Information

Patent Citations

  • Portable radio communication unit

    JP1979029948A

  • Corrosion inhibitor composition for metal, resin composition comprising the same and molding thereof

    JP2007308726A

  • Rust-proof packaging material

    JP2010052751A

  • Rust-proof packaging material

    JP2010254350A

  • Package

    JP2021147086A